The Johns Hopkins Activity and Mobility Promotion Program: A Framework to Increase Activity and Mobility Among Hospitalized Patients. Issue 2 (3rd April 2023) - McLaughlin, Kevin H.; Friedman, Michael; Hoyer, Erik H.; Kudchadkar, Sapna; Flanagan, Eleni; Klein, Lisa; Daley, Kelly; Lavezza, Annette; Schechter, Nicole; Young, Daniel
Abstract : Background: Greater mobility and activity among hospitalized patients has been linked to key outcomes, including decreased length of stay, increased odds of home discharge, and fewer hospital-acquired morbidities. Systematic approaches to increasing patient mobility and activity are needed to improve patient outcomes during and following hospitalization. Problem: While studies have found the Johns Hopkins Activity and Mobility Promotion (JH-AMP) program improves patient mobility and associated outcomes, program details and implementation methods are not published. Approach: JH-AMP is a systematic approach that includes 8 steps, described in this article: (1) organizational prioritization; (2) systematic measurement and daily mobility goal; (3) barrier mitigation; (4) local interdisciplinary roles; (5) sustainable education and training; (6) workflow integration; (7) data feedback; and (8) promotion and awareness. Conclusions: Hospitals and health care systems can use this information to guide implementation of JH-AMP at their institutions.